Development and Psychometric Properties of the Synthetic Drug Dependence Scale in a Chinese Sample - Li, Mei-Ting; Zhang, Jun; Zhang, Dong-Cheng; Che, Qing-Qing; Liu, Ze-Lan; Yang, Pei-Wen; Luo, Xin-Wei; Cai, Tai-Sheng (Frontiers in Psychology, 2021)
Objective: In contrast to the drug situation in the rest of the world, synthetic drugs, rather than traditional drugs, have been the dominant abused drugs in China since 2019. However, the public misconception that synthetic drugs are not as addictive as traditional drugs, such as opioids, as well as the scarcity of specific measurement instruments, has hindered the clinical diagnosis and treatment of synthetic drug abusers, thus the development of a localized instrument to evaluate dependence on synthetic drugs is in urgently needed. Method: Using a sample of 618 Chinese synthetic drug abusers (Mean age = 34.69 years; 44.17% female),the present study developed and examined the psychometric properties of a self-reporting instrument, the Synthetic Drug Dependence Scale (SDDS), which consists of four subscales: Physical dependence, psychological dependence, health injury, and social function injury. Results: The SDDS revealed a four-factor model structure (standardized root mean square residua (SRMR) = 0.039, comparative fit index (CFI) = 0.965, Tucker–Lewis index (TLI) = 0.949, and Root mean square error of approximation (RMSEA) = 0.049), with good internal consistency (Composite Reliability = 0.881, Alpha = 0.801) and convergent validity. Elevated scores on the SDDS were associated with a higher level of reward sensitivity and punishment sensitivity, and stronger impulsivity. Interestingly, psychological dependence was the only significant predictor (p < 0.05) of criterion variables compared with the other three subscales, implying the important role of psychological factors in synthetic drugs dependence. Adequate measurement equivalence across sex, age (18–30 and 31–57 years old) and employment group (employed and unemployed) was also established. Conclusions: The SDDS appears to be an effective and reliable instrument that could be used to further investigate the characteristics of synthetic and traditional drug dependence, promoting a deeper understanding of the physical and psychological roles in drug dependence.